Concentration of Total petroleum Hydrocarbons and Selected Heavy Metals In Soil And plant nearby Al-Nassiriya oil Refinery South of Iraq - Noora k.k.; Bassim y. AL-khafaji (University of Thi-Qar Journal of Science, 2019)
The present study deal with measure concentration of Total petroleum hydrocarbons (TPHs) and selected heavy metals (HMs) (Cd , Pb , Co , V, and Ni) in soil and plant phragmits austriles (cav.) nearby AL-Nassiriya  oil  refinery during  the period extended from winter up to summer 2018 . Some environmental  factors  such as , pH, salinity‰ , Electrical conductivity (Ec.) and soil temperature were measured , also total organic carbon (Toc) % content in soil was determined, and soil texture was  analyzed and  both  of  them expressed as percentage . The result observed  that the  range of the following factors were : soil temp. ranged  from (26-36) ◦c , pH (7.3-7.9) , Ec. (14.3-25.3) µs/cm  and  salinity (5.1-7.3)‰ ,  while the  value  of Toc  ranged from (0.7-8.55)% , soil texture was silty soil in control  station , but they were sandy soil at polluted  stations . The mean concentration  of TPHs  in soil , St.1 , St.2 , St.3  and St.4 were (16.47 ,14.78 ,12.65 and 1.36) µg /gm   dry weight  respectively , while  the mean concentration of HMs in the soil for both season were Cd (0.78 ), Pb (26.85), Co (26.83), Ni (227.17)   and V (95.67)  µg /gm  dry  weight . In  plant (shoot and root) part , mean concentration  of TPHs were (4.86 and 8 .44) µg /gm  dry  weight  respectively ,whereas the mean concentration of heavy metals in both  parts  for both seasons were Cd (0.49 and 0.65) , Pb (30.36 and 49.25) , Co (3.08 and 5.36 , Ni (8.01and 20 .38) and V (1.10 and 1.94) µg /gm dry weight respectively . It concluded  from  the  present  study that the  oil  refinery  waste discharge  affected upon  the soil  and  plant of  the study  area  through  the increase  in concentration of TPHs  and HMs in its, also  significant correlation observed between both pollutants and Toc content.